Implementación de un sistema RFID para el control de la salud y bienestar en el centro de rescate animal CRIAR- Riobamba - Pilatuña Aguagallo, Mauricio Daniel (2023)
The purpose of this research project is the implementation of an RFID System in the Riobamba Comprehensive Animal Rescue Center to monitor the health and well-being of the dogs for which the center is responsible. For the execution, RFID readers with UHF frequency and RFID tags were placed on a collar, and another proportion implanted with a microchip was installed. Through a website, essential data about the animal to control its health and care was found to improve its quality of life. The emitted signal will be captured by two RFID readers, and through so-called Triangulation of the angles of incidence to know the location of the RFID tag; this mathematical process will make it easier for us to control its security and identify the tag that is leaving that perimeter. As a final complement for a unique recognition of each tag and microchip placed on each animal that is responsible for BREEDING, qualified personnel have access to an IOT platform where all the data will be visualized and edited for their daily control of each animal in the same way. The people responsible for the animals that come up for adoption can view their status and health control using an entry code. This process will be validated with the results, reducing the number of animals that have died inside and outside of CRIAR with constant monitoring of their health.